Antecedents of Digitalization of Bank Products in Increasing Customer Satisfaction : An Economic Perspective - Prabawati, Ni Putu Sinta; Maradona, Agus Fredy (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to find out and analyze the effect of comfort on increasing customer satisfaction, to know and analyze the functional effect on increasing customer satisfaction, to find out and analyze the effect of digital service quality on increasing customer satisfaction, to find out and analyze the effect of employee customoer engagement on increasing customer satisfaction. This study uses a quantitative research method. The results of the study showed that comfort had a positive and significant effect on consumer satisfaction, which meant that H1 was accepted. Functional has a positive and significant effect on consumer satisfaction, which means that H2 is accepted. Digital service quality has a positive and significant effect on consumer satisfaction, which means that H3 is accepted. Employee customer engagement has a positive and significant effect on consumer satisfaction, which means that H4 is accepted.